2018
DOI: 10.1186/s13071-018-2617-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tools in childhood malaria

Abstract: Every year, millions of people are burdened with malaria. An estimated 429,000 casualties were reported in 2015, with the majority made up of children under five years old. Early and accurate diagnosis of malaria is of paramount importance to ensure appropriate administration of treatment. This minimizes the risk of parasite resistance development, reduces drug wastage and unnecessary adverse reaction to antimalarial drugs. Malaria diagnostic tools have expanded beyond the conventional microscopic examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 103 publications
2
48
0
Order By: Relevance
“…2 ) [ 22 , 23 ]. Reports show that HRP2 gene deletion in endemic areas, lead to absence of HRP2 antigens causing negative result with RDT [ 24 ]. However WHO, making a pronouncement on the issue of HRP2 genetic causing false negative RDT result, stated that HRP2 gene deletion might not be the main cause of false negative but rather malfunctioning RDTs due to poor storage and transport condition, operator errors and poor quality RDTs [ 25 ].…”
Section: Main Textmentioning
confidence: 99%
“…2 ) [ 22 , 23 ]. Reports show that HRP2 gene deletion in endemic areas, lead to absence of HRP2 antigens causing negative result with RDT [ 24 ]. However WHO, making a pronouncement on the issue of HRP2 genetic causing false negative RDT result, stated that HRP2 gene deletion might not be the main cause of false negative but rather malfunctioning RDTs due to poor storage and transport condition, operator errors and poor quality RDTs [ 25 ].…”
Section: Main Textmentioning
confidence: 99%
“…Currently, several types of malaria diagnostic methods are available including light microscopy, rapid diagnostic tests (RDTs) and polymerase chain reaction (PCR) assay. In Malaysia, light microscopy examination of blood slides is the primary method in malaria diagnosis [ 17 , 18 ]. This method remains the gold standard for malaria diagnosis and has clear advantages; it is inexpensive and allows for identification and quantification of malaria species [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that higher historical forest loss could be one of the factors that signi cantly associated with higher incidence of P. knowlesi infection in Malaysia (12)(13)(14)(15)(16) Currently, several types of malaria diagnostic methods are available including light microscopy, rapid diagnostic tests (RDTs) and polymerase chain reaction (PCR) assay. In Malaysia, light microscopy examination of blood slides is the primary method in malaria diagnosis (17,18). This method remains the gold standard for malaria diagnosis and has clear advantages which are inexpensive, allows identi cation and quanti cation of malaria species (19,20).…”
Section: Introductionmentioning
confidence: 99%